Grito por el Derecho a la Educación en Chile. Marcha de los Paraguas y movilización estudiantil de 2011 (Altre Modernità, 2016)
The paper analyzes the political meaning of the cry for the right to education, in the context of the student movement of 2011 in Chile. The premise supports the idea that a cry runs through Chilean society during the student movement during 2011, denouncing the responsibility of the educational policy in the violation of the right to education and announcing the urgency of recovering public education. This cry is in line with the New Social Movements that, by opposing the prevailing order, expand the political frame. During this study, documentary research was used in addition to a range of written, iconographic, oral and musical sources, in harmony with the pulse of the street, place of re-politicization. OnThe conclusions emphasize the political meaning of the Chilean student movement of 2011 as an expression of the New Social Movements. New social individuals denounce the magnitude of the educational inequality in the Chilean educational system, as well as the responsibility of the official educational policy in the weakening of the State guarantee for education, by the implementation of 3 main devices: the role of the subsidizing State, demand-side financing and educative standardization (technical Ð traditional curriculum and the National Education Quality Measurement System). The Chilean student movement of 2011 is a sign of historical contingency, of collective and social mobilization that fights against neoliberal order.  The article ends by encouraging a Policy of Reparation, because dreams are projects we fight for and utopia gives life to hope.